Phylogeography and genetic diversity of the widespread katydid Ducetia japonica (Thunberg, 1815) across China - Zhi‐Jun Zhou; Yun‐Xia Zhen; Bei Guan; Lan Ma; Wen‐Jing Wang (Ecology and Evolution, 2021)
Abstract Habitat fragmentation can lower migration rates and genetic connectivity among remaining populations of native species. Ducetia japonica is one of the most widespread katydids in China, but little is known about its genetic structure and phylogeographic distribution. We combined the five‐prime region of cytochrome c oxidase subunit I (COI‐5P), 11 newly developed microsatellite loci coupled with an ecological niche model (ENM) to examine the genetic diversity and population structure of D. japonica in China and beyond to Laos and Singapore. Both Bayesian inference (BI) and haplotype network methods revealed six mitochondrial COI‐5P lineages. The distribution of COI‐5P haplotypes may not demonstrate significant phylogeographic structure (NST > GST, p > .05). The STRUCTURE analysis based on microsatellite data also revealed six genetic clusters, but discordant with those obtained from COI‐5P haplotypes. For both COI‐5P and microsatellite data, Mantel tests revealed a significant positive correlation between geographic and genetic distances in mainland China. Bayesian skyline plot (BSP) analyses indicated that the population size of D. japonica's three major mitochondrial COI‐5P lineages were seemingly not affected by last glacial maximum (LGM, 0.015–0.025 Mya). The ecological niche models showed that the current distribution of D. japonica was similar to the species’ distribution during the LGM period and only slightly extended in northern China. Further phylogeographic studies based on more extensive sampling are needed to identify specific locations of glacial refugia in northern China.